2016
DOI: 10.1140/epjc/s10052-016-4311-6
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic geometry of black holes in f(R) gravity

Abstract: In this paper, we consider three types (static, static charged, and rotating charged) of black holes in f (R) gravity. We study the thermodynamical behavior, stability conditions, and phase transition of these black holes. It is shown that the number and type of phase transition points are related to different parameters, which shows the dependency of the stability conditions to these parameters. Also, we extend our study to different thermodynamic geometry methods (Ruppeiner, Weinhold, and GTD). Next, we inve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…In this section, we study the geometric structure of Weinhold, Ruppiner, Quevedo and HPEM formalisms, and investigate phase transition of a charged AdS black hole with a global monopole. The Weinhold geometry is specified in mass representation as [19] g W ij = ∂ i ∂ j M (S, l, Q), (4.1) and the line element for a charged AdS black hole with a global monopole is given by [30]…”
Section: Thermodynamic Geometrymentioning
confidence: 99%
“…In this section, we study the geometric structure of Weinhold, Ruppiner, Quevedo and HPEM formalisms, and investigate phase transition of a charged AdS black hole with a global monopole. The Weinhold geometry is specified in mass representation as [19] g W ij = ∂ i ∂ j M (S, l, Q), (4.1) and the line element for a charged AdS black hole with a global monopole is given by [30]…”
Section: Thermodynamic Geometrymentioning
confidence: 99%
“…According to Ruppeiner's proposal, the Riemannian geometry could give insight into the underly-ing statistical mechanical system. Inspired by the close connection with phase transitions, thermodynamic state space geometry has been extensively adopted for black hole research [53,65,[73][74][75][76][77][78][79]. To begin with, the metric defined by Ruppeiner [64] is given by…”
Section: Thermodynamic State Space Geometry and Microscopic Propermentioning
confidence: 99%
“…gravity. In view of this, various investigations have been discussed with respected to the thermodynamics in the f (R) spacetimes [48][49][50][51]. In these studies, they found that the laws of thermodynamics of f (R) black hole was true.…”
Section: Introductionmentioning
confidence: 99%